Functional Diversification of FD Transcription Factors in Rice, Components of Florigen Activation Complexes - Tsuji, Hiroyuki (Oxford University Press, 2013)
Florigen, a protein encoded by the FLOWERING LOCUS T (FT) in Arabidopsis and Heading date 3a (Hd3a) in rice, is the universal flowering hormone in plants. Florigen is transported from leaves to the shoot apical meristem and initiates floral evocation. In shoot apical cells, conserved cytoplasmic 14-3-3 proteins act as florigen receptors. A hexameric florigen activation complex (FAC) composed of Hd3a, 14-3-3 proteins, and OsFD1, a transcription factor, activates OsMADS15, a rice homolog of Arabidopsis APETALA1, leading to flowering. Because FD is a key component of the FAC, we characterized the FD gene family and their functions. Phylogenetic analysis of FD genes indicated that this family is divided into two groups: (i) canonical FD genes that are conserved among eudicots and non-Poaceae monocots; and (ii) Poaceae-specific FD genes that are organized into three subgroups: Poaceae FD1, FD2 and FD3. The Poaceae FD1 group shares a small sequence motif, T(A/V)LSLNS, with FDs of eudicots and non-Poaceae monocots. Overexpression of OsFD2, a member of the Poaceae FD2 group, produced smaller leaves with shorter plastochrons, suggesting that OsFD2 controls leaf development. In vivo subcellular localization of Hd3a, 14-3-3 and OsFD2 suggested that in contrast to OsFD1, OsFD2 is restricted to the cytoplasm through its interaction with the cytoplasmic 14-3-3 proteins, and interaction of Hd3a with 14-3-3 facilitates nuclear translocation of the FAC containing OsFD2. These results suggest that FD function has diverged between OsFD1 and OsFD2, but formation of a FAC is essential for their function.